ANALYSIS OF THE EFFECT OF DISCIPLINE, JOB SATISFACTION, AND WORK MOTIVATION, TO EMPLOYEE PERFORMANCE AT PT. POS INDONESIA, CENTRAL JAKARTA BRANCH - Muhammad Abdul Muis; Amrison Amrison (Dinasti International Journal of Education Management And Social Science, 2021)
This study aimed to analyze the effect of discipline, job satisfaction, and work motivation on employee performance at PT. Pos Indonesia,Central Jakarta Branch The research methodology used a quantitative method with cross-section data and primary data obtained from questionnaires. Mechanical sampling using a purposive sampling method with the data in 2019. The data analysis technique used is multiple linear regression to test the validity, reliability test, the test model stability, linearity test, normality test, classic assumption test (multicollinearity test, heteroscedasticity test) and hypothesis testing t-statistic and f-statistic to examine the effects together with a significance level of 5%. The results of this study showed that in partial variable Motivation of work, Discipline, and Job Satisfaction has a positive and significant impact on the Satisfaction of Employee Performance. Meanwhile, the independent variable of Motivation of work, Discipline, and Job Satisfaction with together have a significant relationship to the dependent variable, Satisfaction of Employee Performance. Coefficient of determination from this study showed 72.03% result, it shows that the variation of the independent variables are Motivation of work, Discipline and Job Satisfaction can explain the rise and fall of the dependent variable variation Satisfaction of Employee Performance is 72.03%, while the remaining 27.97% affected by other independent variables.